Path Analysis on the Deterninants of Health Cadres Ability in Early Detection and Management of Pregnancy Risk Factors in Sleman, Yogyakarta, Indonesia - Istri Yuliani; Bhisma Murti; Endang Sutisna Sulaeman; Tedjo Danudjo Oepomo (Journal of Health Policy and Management, 2019)
Background: Every pregnant woman has the potential to experience risk, so it is necessary to get serious attention and special treatment by health workers, family, and community. One role of the community is as the health cadres. This study aimed to examine the determinants of health cadre ability in early detection and management of pregnancy risk factors.Subjects and Method: The research used quantitative method and cross-sectional approach. There were 269 health cadres participating as research samples. The sampling technique used is multistage cluster random sampling. Data were collected using a questionnaire with a Likert scale. Data analysis is done using path analysis.Results: Cadre’s ability in early detection of pregnancy risk factors was affected by attitude (b= 0.38; SE=0.10; p<0.001), experience (b=0.38; SE=0.10; p<0.001), motivation (b=0.63; SE=0.14; p<0.001), compensation (b=0.68; SE=0.19; p<0.001), workload (b=0.64; SE=0.23; p= 0.005), education and training (b=0.68; SE=0.19; p=0.001), supervision (b=0.99; SE=0.17; p<0.001), perceived seriousness (b=0.73; SE=0.16; p<0.001), and perceived benefit (b=0.84; SE=0.18; p<0.001). Cadre’s ability in the management of pregnancy risk factors was affected by attitude (b= 0.54; SE= 0.12; p<0.001), experience (b= 0.18; SE= 0.10; p= 0.079), motivation (b=0.36; SE=0.15; p=0.014), compensation (b=0.64; SE=0.20; p=0.001), supervision (b = 0.36; (b= 0.49; SE = 0.18; p= 0.008), and early detection of pregnancy risk factors (b= 0.29; SE= 0.05; p<0.001).Conclusion: Cadre’s ability in early detection of pregnancy risk factors is affected by attitude, experience, motivation, compensation, workload, education and training, supervision, perceived seriousness, and perceived benefit. Cadre’s ability in the management of pregnancy risk factors is affected by attitude, experience, motivation, compensation, supervision, and early detection of pregnancy risk factorsKeywords: health cadres, early detection, management, pregnancy risk factors, path analysisCorrespondence: Istri Yuliani. Doctoral Program in Community Development/Empowerment, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: istriyuliani1@gmail.com. Mobile: 08122796697Journal of Health Policy and Management (2019), 4(1): 47-58https://doi.org/10.26911/thejhpm.2019.04.01.06